2017
DOI: 10.1039/c7ay01091e
|View full text |Cite
|
Sign up to set email alerts
|

Paper spray ionization mass spectrometry applied to forensic chemistry – drugs of abuse, inks and questioned documents

Abstract: Paper spray ionization mass spectrometry (PS-MS) technique is a versatile and powerful tool to solve numerous problems in forensic chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 49 publications
0
42
0
2
Order By: Relevance
“…7 The most abundant cannabinoids present in the Cannabis plant are: 9,10 (i) cannabidiol (CBD), an anticonvulsant drug tested in treatments of epileptic patients, 11 in addition to being anxiolytic, anti-inflammatory, antipsychotic, antispasmodic and analgesic; 12 (ii) cannabigerol (CBG), which has antiproliferative and antiglaucoma activities 13 as well as antibiotic, anti-inflammatory, antifungal and analgesic activities; 12 (iii) cannabinol (CBN), 1 a sedative and anticonvulsant that is anti-inflammatory; 12 (iv) cannabichromene (CBC), which is anti-inflammatory, antifungal and analgesic; 12 and (v) Δ 9 -tetrahydrocannabinol (Δ 9 -THC), the main psychoactive compound of the Cannabis plant. 1,[14][15][16][17][18] Most cannabinoids have a 21 carbon atom structural feature, with possible variations in the length of their side chains (C1-C5) attached to the aromatic ring. In the most common homologs, the n-pentyl side chain is replaced by n-propyl, and these analogues are named using the suffix "varin", for example, Δ 9 -tetrahydrocannabivarin (Δ 9 -THCV), cannabidivarin (CBDV) and cannabinovarin (CBNV).…”
Section: Introductionmentioning
confidence: 99%
“…7 The most abundant cannabinoids present in the Cannabis plant are: 9,10 (i) cannabidiol (CBD), an anticonvulsant drug tested in treatments of epileptic patients, 11 in addition to being anxiolytic, anti-inflammatory, antipsychotic, antispasmodic and analgesic; 12 (ii) cannabigerol (CBG), which has antiproliferative and antiglaucoma activities 13 as well as antibiotic, anti-inflammatory, antifungal and analgesic activities; 12 (iii) cannabinol (CBN), 1 a sedative and anticonvulsant that is anti-inflammatory; 12 (iv) cannabichromene (CBC), which is anti-inflammatory, antifungal and analgesic; 12 and (v) Δ 9 -tetrahydrocannabinol (Δ 9 -THC), the main psychoactive compound of the Cannabis plant. 1,[14][15][16][17][18] Most cannabinoids have a 21 carbon atom structural feature, with possible variations in the length of their side chains (C1-C5) attached to the aromatic ring. In the most common homologs, the n-pentyl side chain is replaced by n-propyl, and these analogues are named using the suffix "varin", for example, Δ 9 -tetrahydrocannabivarin (Δ 9 -THCV), cannabidivarin (CBDV) and cannabinovarin (CBNV).…”
Section: Introductionmentioning
confidence: 99%
“…methanol (CH 3 OH) or acetonitrile (ACN), fiber tip shape, and distance of fiber tip to mass spectrometer inlet ( Figure 1B). The standard conditions were evaluated by fixing the volume of sample and spray solvent as 10 and 20 μL, respectively, which are often used in PSI-MS. 8,15 The experiments showed the increase of total ion current (TIC) values producing greater stability of analyte signal and better ionization efficiency while reducing the effect of the background. Spray voltage lower than 2.5 kV produced an unstable ionization process during the analysis, while voltages higher than 4.0 kV showed higher background noise.…”
Section: Optimization Of Fsi-ms Conditionsmentioning
confidence: 99%
“…Spray voltage lower than 2.5 kV produced an unstable ionization process during the analysis, while voltages higher than 4.0 kV showed higher background noise. Thus, a spray voltage of 3.5 kV was chosen for both positive and negative ion modes of ionization, which represents a voltage commonly applied in PSI-MS. 8,22 The blank PP fiber was then analyzed by FSI(+) to determine the optimal spray solvent (methanol or acetonitrile).…”
Section: Optimization Of Fsi-ms Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the authors recommend to be careful with the low sensitivity of this technique that was observed to possibly occur due to an ionic suppression process, caused by the matrix effect (extracted impurities from the surface of the blotter paper). The results provided a limit of detection of around 0.17 ppb [ 47 ].…”
Section: Current Analytical Approaches To Target Analysesmentioning
confidence: 99%